The effect of musical fit on consumers’ preferences between competing alternate petrols - Yeoh, J. (Sage Publications Ltd., 2012)
Music that ‘fits’ with the attributes of commercial products should raise the salience of those products over others, and therefore prime their selection. Participants were presented with two advertisements for two competing petrol brands, which featured music that did (not) fit with those brands. Brand preferences were not affected by the advertisements among participants who were regular users of one of the brands. However, participants who were not regular users of either brand demonstrated a preference for the brand advertised with music that ‘fitted’ the brand attributes. This demonstrates that musical ‘fit’ can influence product choice when consumers do not have a clear existing preference for one product over another, but is otherwise of limited commercial value.